Modified lithium oxide-based prelithium reagent, method for preparing same, and use thereof
Patent Information
- Application Number
- CN202510466861.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-10-23
AI Technical Summary
然而,相比于应用在电解水分解、环境处理、化学合成和石化炼油中等,含钴催化剂对于氧化锂阴极预锂剂在电极中的固相分解反应的催化应用很少涉及
采用含钴的磷化合物作为改性剂,与氧化锂混合后通过球磨法制备出改性的近乎单一晶相的高性能氧化锂基预锂剂,这种方法完全避免了高温固相处理过程,且制备的氧化锂基预锂剂具有大于800 mAh g-1高达1000 mAh g-1以上(~预锂剂全质量)的实际预锂比容量和大于85%的预锂效率(~理论预锂容量),是极优良的阴极添加剂,应用于锂离子电池的添加量可以小于等于2 wt.%,且可以在对组装电池不产生负面影响的情况下完成首次充电预锂。
Smart Images

Figure CN122968281A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lithium batteries, specifically relating to the modification of lithium oxide prelithiating agents. Background Technology
[0002] Cathode pre-lithiation technology aims to compensate for the reversible lithium-ion loss during the charging and discharging process of lithium-ion batteries, thereby further improving the energy density of the cathode. Lithium oxide, as a cathode pre-lithiation agent, has a theoretical pre-lithiation capacity as high as 1794 mAh g⁻¹. -1 Furthermore, compared to cathode pre-lithiation agents primarily composed of transition metal oxides (Li6CoO4, Li2NiO2, and Li5FeO4), lithium oxide decomposition products consist solely of oxygen, without the formation of inert solid residues. However, in practical applications, its lithium release reaction voltage exceeds 4.7V. vs Li / Li + This is far higher than the cutoff voltage of the lithium-ion battery cathode, ultimately resulting in a pre-lithiation specific capacity of less than 100 mAh g. -1 Or the pre-lithiation efficiency is less than 5 wt.%.
[0003] Cobalt, as a transition metal, possesses certain catalytic properties, including cobalt-based catalysts (Co / Al2O3, Co / SiO2), cobalt oxides (Co3O4), cobalt phosphides (Co2P), cobalt phosphates (Co3(PO4)2), cobalt-nitrogen-doped carbon materials (Co-NC), and cobalt complexes (cobalt porphyrin, cobalt Schiff base complexes). However, compared to its applications in water electrolysis, environmental treatment, chemical synthesis, and petrochemical refining, the catalytic application of cobalt-containing catalysts in the solid-phase decomposition reaction of lithium oxide cathode pre-lithiation agents in electrodes is rarely explored. Summary of the Invention
[0004] To address the aforementioned technical problems, the present invention aims to provide a high-performance lithium oxide-based cathode pre-lithiation agent modified with a nearly single-crystal phase and containing a cobalt phosphorus compound without a high-temperature solid-phase process, and its preparation method.
[0005] To achieve the above objectives, the present invention proposes the following solution: Firstly, a method for preparing a lithium oxide-based pre-lithiation agent is provided, including: Lithium oxide and a modifier were ball-milled under an inert atmosphere to obtain a lithium oxide-based pre-lithiation agent; the modifier was a cobalt-containing phosphorus compound.
[0006] Furthermore, the cobalt-containing phosphorus compound is one or more of cobalt phosphate (Co3(PO4)2), cobalt metaphosphate (Co(PO3)2), cobalt pyrophosphate (Co2(P2O7)), lithium cobalt phosphate (LiCoPO4), and cobalt phosphide (Co2P).
[0007] Furthermore, the cobalt-containing phosphorus compound is mixed with lithium oxide at a molar ratio of Co to Li of 1:14 to 1:22.
[0008] Furthermore, the particle size D50 of the modifier is not greater than 8 μm.
[0009] Furthermore, the ball milling is a dry ball milling process.
[0010] Furthermore, an inert atmosphere is maintained in the grinding jar throughout the ball milling process.
[0011] Furthermore, the ball milling is intermittent ball milling.
[0012] Furthermore, the duration of the intermittent ball milling is 600~1400 min.
[0013] Furthermore, the intermittent ball milling procedure is to work for 3-6 minutes and then rest for 1-4 minutes.
[0014] Furthermore, the ball mill uses zirconium dioxide grinding balls, and the size and mass ratio of the zirconium dioxide grinding balls is 3 mm:2 mm:0.6~0.8 mm:0.2~0.3 mm=1:1:1:1 or 3 mm:0.2~0.3 mm=1:1.
[0015] Further, the ball milling of lithium oxide and modifier under an inert atmosphere comprises: S1. Lithium oxide and modifier are ball-milled under an inert atmosphere to obtain a preliminary mixture. S2. The initial mixture is ball-milled under an inert atmosphere to obtain a modified lithium oxide-based prelithiating agent.
[0016] Furthermore, in step S1, the rotational speed of the ball mill is 300-800 rpm.
[0017] Furthermore, in step S1, the ball milling time is 300-500 minutes.
[0018] Furthermore, in step S2, the rotational speed of the ball mill is 400-800 rpm.
[0019] Furthermore, in step S2, the ball milling time is 300-900 min.
[0020] Furthermore, before the ball milling mixture in step S2 and after the ball milling mixture in step S1, a scraping step under an inert atmosphere is also included.
[0021] Furthermore, in step S2, a sieving post-treatment is included after ball milling the mixture; the sieve used for the sieving post-treatment has a mesh size of 200 to 400 mesh.
[0022] Secondly, a lithium oxide-based prelithiation agent is provided, which is prepared using the aforementioned preparation method.
[0023] Thirdly, an electrode is provided comprising the aforementioned lithium oxide-based prelithiating agent.
[0024] Fourthly, a lithium-ion battery is provided, comprising the aforementioned electrodes.
[0025] Compared with the prior art, the present invention has the following beneficial effects: A high-performance lithium oxide-based pre-lithiation agent with a near-monocrystalline phase was prepared by ball milling using a cobalt-containing phosphorus compound as a modifier and mixed with lithium oxide. This method completely avoids the high-temperature solid-state treatment process, and the prepared lithium oxide-based pre-lithiation agent has a strength greater than 800 mAh g⁻¹. -1 Up to 1000 mAh g -1 The above (~ total mass of pre-lithiation agent) actual pre-lithiation specific capacity and pre-lithiation efficiency greater than 85% (~ theoretical pre-lithiation capacity) make it an excellent cathode additive. The amount added to lithium-ion batteries can be less than or equal to 2 wt.%, and the first charge pre-lithiation can be completed without negatively affecting the assembled battery. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 X-ray diffraction patterns of the materials prepared in Example 1 and Comparative Example 1.
[0028] Figure 2 Scanning electron microscope images of the materials prepared in Example 1 and Comparative Example 1.
[0029] Figure 3 The first charge curves of the coin cells assembled from the materials prepared in Example 1 and Comparative Example 1 are shown.
[0030] Figure 4 The first charge curves of the coin cells assembled from the materials prepared in Example 1 and Comparative Example 2 are shown.
[0031] Figure 5 Cycle performance graph of coin cells assembled with cathode materials prepared in Example 1 with 0% and 2% pre-lithiating agent.
[0032] Figure 6The first charge curves of the coin cells assembled from the materials prepared in Examples 1 to 6 are shown. Detailed Implementation
[0033] To address the problem of excessively high lithium release voltage leading to poor lithium replenishment when lithium oxide is used as a pre-lithiation cathode additive, the applicant has discovered that mixing lithium oxide with a phosphorus-containing cobalt compound and then ball-milling yields a high-performance, single-phase lithium oxide-based pre-lithiation agent modified with a modifier. This process eliminates the need for a high-temperature solid-phase reaction, and the prepared lithium oxide-based pre-lithiation agent exhibits extremely high actual pre-lithiation specific capacity and pre-lithiation efficiency, while requiring a relatively low addition amount in the cathode of lithium-ion batteries. Based on this, the present invention has been completed.
[0034] This invention provides a method for preparing a modified lithium oxide-based pre-lithiation agent, comprising: Lithium oxide and a modifier were ball-milled under an inert atmosphere to obtain a modified lithium oxide-based pre-lithiation agent; the modifier was a cobalt-containing phosphorus compound.
[0035] In some preferred embodiments, the cobalt-containing phosphorus compound is one or more of cobalt phosphate (Co3(PO4)2), cobalt metaphosphate (Co(PO3)2), cobalt pyrophosphate (Co2(P2O7)), lithium cobalt phosphate (LiCoPO4), and cobalt phosphide (Co2P).
[0036] To lower the reaction energy barrier in the lithium oxide decomposition process that releases lithium ions, a phosphorus-containing cobalt compound was introduced as a catalyst to enhance the reaction kinetics. Simultaneously, drawing on experience in catalyst research where increasing the specific surface area in contact with reactants improves catalytic performance, this invention utilizes ball milling technology to thoroughly break down the primary particles of the material. During the research, it was discovered that the localized micro-stress and micro-heat generated by the friction between the material and the milling balls during ball milling can effectively destroy the crystalline phase of the phosphorus-containing cobalt compound and react with lithium oxide, allowing cobalt to enter the lithium oxide lattice and fully exert its catalytic effect. This ultimately yields a high-performance lithium oxide-based cathode pre-lithiation agent containing a single crystalline phase with a large amount of amorphous structure, solving the problem of excessively high lithium oxide release voltage and significantly improving the reaction kinetics of lithium oxide decomposition and lithium release. This results in ultra-high actual pre-lithiation specific capacity and efficiency, as well as ultra-low pre-lithiation addition, bringing it closer to practical production applications.
[0037] If the particle size of the modifier is too large, it will be difficult for cobalt to enter the lithium oxide lattice and it will be easy to be unevenly distributed, which will affect the catalytic performance. In some preferred embodiments, the particle size D50 of the modifier is not greater than 8 μm.
[0038] In some preferred embodiments, the cobalt-containing phosphorus compound is mixed with lithium oxide at a Co to Li molar ratio of 1:14 to 1:22, such as 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, etc. Studies have found that when the Co to Li molar ratio is below 14, not only is the cost of the cobalt source quite high, but it also affects the theoretical pre-lithiation capacity. When the molar ratio is above 22, not only is the pre-lithiation efficiency reduced, but the plateau increases by more than 4.5V.
[0039] In some preferred embodiments, the ball milling is a dry ball milling method, which significantly increases the friction between the powder and the zirconium beads, increases local micro-stress and local micro-heat, thereby improving the reactivity of the material.
[0040] In some embodiments, an inert atmosphere is maintained in the grinding jar during ball milling; alternatively, the inert atmosphere may be high-purity argon or other inert gases that do not contain water or oxygen.
[0041] In some preferred embodiments, the ball milling is an intermittent ball milling. The applicant has found through research that intermittent ball milling helps to avoid powder agglomeration and excessively high temperature inside the tank, thereby improving the degree of material reaction and the uniformity of primary particle distribution.
[0042] In some preferred embodiments, the duration of the intermittent ball milling is 600~1400 min, for example 600 min, 650 min, 700 min, 750 min, 800 min, 850 min, 900 min, 950 min, 1000 min, 1050 min, 1100 min, 1150 min, 1200 min, 1300 min, 1400 min, etc.
[0043] In some preferred embodiments, the intermittent ball milling process involves working for 3-6 minutes and then resting for 1-4 minutes.
[0044] In some embodiments, the grinding beads in the ball mill are zirconium beads.
[0045] The applicant discovered through research that ball milling using conventional single-size grinding balls can prepare pre-lithiated materials with a capacity of 800 mAh g. -1The above (~ total mass of pre-lithiating agent) actual pre-lithiation specific capacity solves the technical problem to be solved in this application. Based on this, the applicant, through further optimization research, discovered that using grinding balls of different sizes is more conducive to the primary particle refinement of the powder, with larger grinding balls providing higher local impact energy and smaller grinding balls providing more local friction surface area. In a partially preferred embodiment, the size and mass ratio of the zirconia grinding balls used in the initial mixing and grinding is 3 mm:2 mm:0.6~0.8 mm:0.2~0.3 mm=1:1:1:1 or 3 mm:0.2~0.3 mm=1:1.
[0046] In some preferred embodiments, the ball milling of lithium oxide and the modifier under an inert atmosphere includes: S1. Lithium oxide and modifier are ball-milled under an inert atmosphere to obtain a preliminary mixture. S2. The initial mixture is ball-milled under an inert atmosphere to obtain a modified lithium oxide-based prelithiating agent.
[0047] The ball milling in step S1 can use either a low or high ball milling speed, such as 300~800 rpm, for example 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc. However, a relatively low ball milling speed can reduce costs. In some preferred embodiments, the ball milling speed in step S1 is 300~500 rpm.
[0048] In order to achieve the modification effect, the ball milling in step S2 requires a relatively high ball milling speed. In some preferred embodiments, the ball milling speed in step S2 is 400 to 800 rpm, such as 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., more preferably 500 to 800 rpm, and even more preferably 600 to 800 rpm.
[0049] In step S2, the ball milling time is 300-900 min, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, etc.; in some preferred embodiments, the ball milling time is 700-900 min. The applicant has found through research that the pre-lithiation effect of the pre-lithiation agent prepared by intermittent ball milling time of 700-900 min in step S2 is better.
[0050] In some preferred embodiments, a scraping step under an inert atmosphere is included before ball milling the mixture in step S2 and after ball milling the mixture in step S1. The applicant has found through research that the scraping treatment after initial mixing can improve the pre-lithiation effect of the obtained pre-lithiation agent. Analysis suggests this may be because the scraping treatment can prevent powder agglomeration and improve the reactivity of the material and the uniformity of the primary particle distribution.
[0051] Finally, sieving the obtained compound product can avoid the coating uniformity problem caused by excessively large secondary particles resulting from agglomeration, which is beneficial to improving the kinetics of the cathode reaction and the capacity of the pre-lithiating agent. In some preferred embodiments, the sieve mesh size is 200-400 mesh.
[0052] In some preferred embodiments, in step S2, the particle size of the single-crystal phase high-performance lithium oxide-based cathode pre-lithiation agent modified by the modifier is 200-400 mesh.
[0053] Some embodiments of the present invention provide a high-performance lithium oxide-based prelithiation agent with a single crystalline phase modified by a modifier, which is prepared by the aforementioned preparation method.
[0054] Some embodiments of the present invention provide an electrode, more specifically, a cathode, comprising a high-performance lithium oxide-based prelithiation agent of a single crystalline phase modified by the aforementioned modifier.
[0055] Some embodiments of the present invention provide a lithium-ion battery comprising a high-performance lithium oxide-based pre-lithiation agent of a single crystalline phase modified by the aforementioned electrodes or the aforementioned modifiers.
[0056] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0057] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0058] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0059] Example 1 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co3(PO4)2 are initially mixed at a Li to Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding beads used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0060] Step S2: After scraping the material from the initial mixing and grinding in step S1 under an argon atmosphere, it is then dry-milled again for remixing. The milling process is carried out for 900 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes. The remixed product is then passed through a 200-mesh sieve to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0061] Comparative Example 1 Lithium oxide and Co3(PO4)2 were manually ground and mixed at the same Li / Co molar ratio as in Example 1 to obtain a mixed material.
[0062] Figure 1 The X-ray diffraction patterns of the materials prepared in Example 1 and Comparative Example 1 are shown in the figures. Figure 1 Analysis shows that the dry ball milling in Example 1 altered the composition of the crystalline phase, causing Co and P elements to exist in an amorphous phase or enter the lithium oxide lattice, resulting in nearly single-phase doped lithium oxide.
[0063] Figure 2 Scanning electron microscope images of the materials prepared in Example 1 and Comparative Example 1.
[0064] Comparative Example 2 Step S1: Lithium oxide and Co3(PO4)2 are initially mixed at a Li to Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding beads used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0065] Step S2: After the material from the initial mixing and grinding in step S1 is collected in an argon atmosphere, a high-temperature solid-phase reaction is carried out in a closed atmosphere of high-purity argon: the temperature is maintained at 850℃ for 8 hours, the heating rate is 5℃ / min, and then the temperature is allowed to drop naturally. The obtained material is ball-milled and then sieved through a 200-mesh sieve to obtain a pre-lithiated solid powder material.
[0066] Example 2 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co(PO3)2 are initially mixed at a Li to Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding balls used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0067] Step S2: After scraping the material from the initial mixing and grinding in step S1 under an argon atmosphere, it is then dry-milled again for remixing. The milling process is carried out for 900 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes. The remixed product is then sieved through a 200-mesh sieve to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0068] Example 3 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co2 (P2O7) are initially mixed at a Li:Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding beads used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0069] Step S2: After scraping the material from the initial mixing and grinding in step S1 under an argon atmosphere, it is then dry-milled again for remixing. The milling process is carried out for 900 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes. The remixed product is then sieved through a 200-mesh sieve to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0070] Example 4 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co2P are initially mixed at a Li:Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding balls used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0071] Step S2: After scraping the material from the initial mixing and grinding in step S1 under an argon atmosphere, it is then dry-milled again for remixing. The milling process is carried out for 900 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes. The remixed product is then sieved through a 200-mesh sieve to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0072] Example 5 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co2 (P2O7) are initially mixed at a Li:Co molar ratio of 22:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding balls used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 420 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes.
[0073] Step S2: After scraping the material from the initial mixing and grinding in step S1 under an argon atmosphere, it is then dry-milled again for remixing. The milling process is carried out for 900 minutes in a closed atmosphere of high-purity argon, with a working speed of 600 rpm for 6 minutes and a rest period of 4 minutes. The remixed product is then sieved through a 200-mesh sieve to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0074] Example 6 A method for preparing a high-performance lithium oxide-based cathode pre-lithiation agent includes the following steps: Step S1: Lithium oxide and Co3(PO4)2 (crystalline phase) are initially mixed at a Li to Co molar ratio of 18:1. Dry ball milling is preferred in this step, a grinding method that uses the impact, compression, and friction of grinding balls to pulverize materials. Generally, a ball-to-material ratio of 10:1 is sufficient for dry ball milling. In this step, the size and mass ratio of the zirconium dioxide grinding balls used is 3mm:2mm:0.6~0.8mm:0.2~0.3mm = 1:1:1:1. Grinding is carried out for 660 minutes in a closed atmosphere of high-purity argon, with a working speed of 400 rpm for 6 minutes and a rest period of 4 minutes.
[0075] Step S2: The product of S1 is post-processed to obtain a modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent solid powder material.
[0076] The samples obtained in each embodiment and comparative example were assembled into lithium button half-cells and subjected to electrochemical tests according to the following method: Preparation of pure pre-lithiated electrode: HNBR (hydrogenated nitrile butadiene rubber) was added to NMP (N-methylpyrrolidone) at 6 wt.% to prepare HNBR NMP sol; the pre-lithiated agent, Super P, and binder (HNBR NMP sol) prepared in each example were mixed in a mass ratio of 6:3:1 to form a slurry, and NMP solvent was added to adjust the viscosity to an appropriate level for electrode slurry preparation, thus obtaining the electrode slurry. The slurry was coated onto the surface of aluminum foil, dried in an inert atmosphere, and punched into electrode sheets with a diameter of 10 mm (loading of 2.0–2.5 mg / cm²). 2 ).
[0077] Assembly of lithium button half-cells containing pure pre-lithiated electrodes: In an argon-filled glove box, lithium button half-cells are assembled in the following order: positive electrode shell, prepared pure pre-lithiated electrodes, separator, lithium metal sheet, gasket, spring sheet and negative electrode shell.
[0078] Charging test: The prepared lithium button half-cell was subjected to the first charging capacity test of the positive electrode at 0.1C within a voltage range of 2.8 to 4.6V at 25℃. The test results are shown in Table 1.
[0079] Using NCM811 as the positive electrode active material, positive electrode sheets were prepared, batteries were assembled, and electrochemical tests were conducted by adding or adding pre-lithiating agents: Preparation of the positive electrode: The pre-lithiation agent prepared in Example 1, NCM811 positive electrode material, Super P, and binder (NMP sol of PVDF) were mixed in a mass ratio of 2:78:10:10 to form a slurry. NMP solvent was added to adjust the viscosity to an appropriate level for electrode slurry preparation, resulting in electrode slurry A. NCM811 positive electrode material, Super P, and binder (NMP sol of PVDF) were mixed in a mass ratio of 80:10:10 to form a slurry. NMP solvent was added to adjust the viscosity to an appropriate level for electrode slurry preparation, resulting in electrode slurry B. Using electrode slurry A and electrode slurry B as raw materials, the electrode slurries were electroscraped onto the surface of aluminum foil, dried in an inert atmosphere, and punched into positive electrode sheets A and B with a diameter of 10 mm (loading of 2.0–2.5 mg / cm²). 2 ).
[0080] Battery assembly: Using positive electrode 4 and positive electrode B as positive electrodes, they are assembled into a pair of lithium button half-cells in an argon-filled glove box in the following order: positive electrode shell, positive electrode, separator, lithium metal sheet, gasket, spring sheet and negative electrode shell.
[0081] Charge-discharge test: The prepared lithium button half-cells were charged and discharged at 0.1C within a voltage range of 2.8 to 4.6V at 25℃.
[0082] Table 1 As shown in Table 1, the cathode cells using the modified single-phase high-performance lithium oxide-based cathode pre-lithiation agent prepared in Example 1 exhibited significantly improved initial charge specific capacity, with pre-lithiation capacity efficiency exceeding 89%, while also maintaining a low charging plateau voltage (<4.3V). Comparing the data from Examples 1, 2, 3, and 4 reveals that the type of phosphorus-containing cobalt compound significantly impacts the modification effect of the lithium oxide-based cathode pre-lithiation agent. The pre-lithiation capacity ranking is Co2(P2O7) > Co3(PO4)2 > Co(PO3)2 > Co2P, which largely aligns with the theoretical pre-lithiation capacity ranking. Notably, Co2P's effect is far inferior to other phosphorus-containing cobalt compounds, possibly due to significantly different interactions between Co and P. Comparing the data from Examples 3 and 5 shows that the lithium-cobalt ratio is a crucial factor influencing the pre-lithiation agent's modification effect; a higher cobalt ion content in the bulk phase helps reduce voltage and promotes the pre-lithiation process. Comparing the data from Examples 1 and 6, Example 1 achieved better pre-lithiation agent performance. The above results fully demonstrate that during the dry ball milling process of each embodiment, local micro-stress and local micro-heat enable lithium oxide to fully react with phosphorus-containing cobalt compounds, resulting in a high-performance modified single-phase lithium oxide-based cathode pre-lithiation agent with excellent effects.
[0083] The first charge curves of the coin cells assembled from the materials prepared in Example 1 and Comparative Example 1 at 25°C and 0.1C are shown in the figure. Figure 3 As shown. From Figure 3 Analysis reveals that the charging platform of the battery assembled in Example 1 is around 4.20 V, and the initial lithium replenishment capacity reaches 1121 mAh / g. In contrast, the electrochemical curve of the battery assembled with material 1 in Comparative Example 1 shows almost no lithium replenishment effect at a cutoff voltage of 4.6 V.
[0084] The first charge curves of the coin cells assembled from the materials prepared in Example 1 and Comparative Example 2 at 25°C and 0.1C are shown in the figure below. Figure 4 As shown. From Figure 4 Analysis reveals that, under the same cutoff voltage of 4.3V, the charging plateau of the battery assembled in Example 1 is approximately 4.20V, with an initial lithium replenishment capacity reaching 968.4 mAh / g. In contrast, the battery assembled from materials in Comparative Example 2 only has a capacity of 264.2 mAh / g and does not exhibit a significant charging plateau. This clearly demonstrates that the high-temperature solid-state step has a negative impact on the performance of the pre-lithiating agent.
[0085] The cycling performance of batteries assembled with NCM811 cathodes containing 2 wt% of the pre-lithiating agent in Example 1 and NCM811 cathodes without the pre-lithiating agent in Example 1 at 0.1C is shown in the figure. Figure 5 As shown. From Figure 5Analysis shows that the battery assembled with NCM811 material containing 2 wt% of the pre-lithiating agent in Example 1 achieved an initial lithium charging capacity of 245.9 mAh / g (~69.5% pre-lithiating efficiency), and the cycle performance of the electrode did not show a significant decrease compared to the battery assembled with NCM811 material without the pre-lithiating agent in Example 1. This indicates that only 2 wt% of the modified single-phase high-performance lithium oxide-based cathode pre-lithiating agent can achieve the purpose of initial charging pre-lithiation without causing negative effects.
[0086] The first charge curves of the coin cells assembled from the materials prepared in Examples 1 to 6 at 25°C and 0.1C are shown in the figure below. Figure 6 As shown. From Figure 6 Analysis shows that, considering the combined data of the initial lithium replenishment capacity and the charging platform, the pre-lithiation performance of Example 3 is greater than that of Example 1, which is greater than that of Example 2, which is greater than that of Example 5, which is greater than that of Example 6, which is greater than that of Example 4.
[0087] A comparison of the initial charging curves of the above embodiments and comparative examples reveals that the batteries assembled from the samples prepared in each embodiment have significantly higher specific charging capacities than those assembled from samples using the same raw materials with simple manual mixing (Comparative Example 1) and samples with an added high-temperature solid-phase process (Comparative Example 2). Furthermore, the batteries assembled in each embodiment exhibit a clear charging plateau, unlike the mixtures. The reasons for this phenomenon may be twofold: firstly, dry ball milling allows lithium oxide and phosphorus-containing cobalt compounds to react, generating a new amorphous phase or introducing cobalt into the lithium oxide lattice. Cobalt ions form local catalytic active centers, further enhancing the reactivity of lithium oxide decomposition and activating its high theoretical lithium replenishment capacity. Secondly, the refinement of the primary particles increases the contact area between reactants, allowing the catalytic reaction to proceed fully and improving the kinetics of the lithium replenishment reaction.
[0088] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified lithium oxide-based pre-lithiation agent, characterized in that, include: Lithium oxide and a modifier were ball-milled under an inert atmosphere to obtain a modified lithium oxide-based pre-lithiation agent; the modifier was a cobalt-containing phosphorus compound.
2. The preparation method of the modified lithium oxide-based pre-lithiation agent as described in claim 1, characterized in that, The cobalt-containing phosphorus compound is one or more of cobalt phosphate (Co3(PO4)2), cobalt metaphosphate (Co(PO3)2), cobalt pyrophosphate (Co2(P2O7)), lithium cobalt phosphate (LiCoPO4), and cobalt phosphide (Co2P); The cobalt-containing phosphorus compound and lithium oxide are mixed at a molar ratio of Co to Li of 1:14 to 1:
22. The particle size D50 of the modifier is not greater than 8 μm.
3. The preparation method of the modified lithium oxide-based pre-lithiation agent as described in claim 1, characterized in that, The ball milling method is dry ball milling; Preferably, an inert atmosphere is maintained in the milling jar throughout the ball milling process; Preferably, the ball milling is intermittent ball milling; Preferably, the duration of the intermittent ball milling is 600~1400 min; Preferably, the intermittent ball milling program consists of working for 3-6 minutes and resting for 1-4 minutes. Preferably, the ball mill uses zirconium dioxide grinding balls, and the size and mass ratio of the zirconium dioxide grinding balls is 3 mm:2 mm:0.6~0.8 mm:0.2~0.3 mm=1:1:1:1 or 3 mm:0.2~0.3 mm=1:
1.
4. The preparation method of the modified lithium oxide-based pre-lithiation agent as described in claim 1, characterized in that, The process of ball milling lithium oxide and the modifier under an inert atmosphere includes: S1. Lithium oxide and modifier are ball-milled under an inert atmosphere to obtain a preliminary mixture. S2. The initial mixture is ball-milled under an inert atmosphere to obtain a modified lithium oxide-based prelithiating agent.
5. The preparation method of the modified lithium oxide-based pre-lithiation agent as described in claim 4, characterized in that, In step S1, the rotational speed of the ball mill is 300-800 rpm; In step S1, the ball milling time is 300-500 minutes.
6. The method for preparing the modified lithium oxide-based pre-lithiation agent as described in claim 4, characterized in that, In step S2, the rotational speed of the ball mill is 400-800 rpm; In step S2, the ball milling time is 300-900 min.
7. The preparation method of the modified lithium oxide-based pre-lithiation agent as described in claim 4, characterized in that, Before the ball milling mixture in step S2 and after the ball milling mixture in step S1, a scraping step under an inert atmosphere is also included. In step S2, after ball milling the mixture, a sieving post-treatment is also included; the sieve size for the sieving post-treatment is 200-400 mesh.
8. A modified lithium oxide-based pre-lithiation agent, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 7.
9. An electrode, characterized in that, It includes the modified lithium oxide-based prelithiating agent as described in claim 8.
10. A lithium-ion battery, characterized in that, It includes the electrode as described in claim 9.